Mutational analysis of primary and metastatic colorectal cancer samples underlying the resistance to cetuximab-based therapy - Nemecek, Radim; Berkovcova, Jitka; Radova, Lenka; Kazda, Tomas; Mlcochova, Jitka; Vychytilova-Faltejskova, Petra; Slaby, Ondrej; Svoboda, Marek (OncoTargets and therapy, 2016)
PURPOSE: Although several molecular markers predicting resistance to cetuximab- or panitumumab-based therapy of metastatic colorectal cancer were described, mutations in RAS proto-oncogenes remain the only predictors being used in daily clinical practice. However, 35%-45% of wild-type RAS patients still do not respond to this anti-epidermal growth factor receptor (anti-EGFR) monoclonal antibody-based therapy, and therefore the definition of other predictors forms an important clinical need. The aim of the present retrospective single-institutional study was to evaluate potential genes responsible for resistance to anti-EGFR therapy in relation to mutational analysis of primary versus metastatic lesions. PATIENTS AND METHODS: Twenty-four paired primary and corresponding metastatic tissue samples from eight nonresponding and four responding metastatic colorectal cancer patients treated with cetuximab-based therapy were sequenced using a next-generation sequencing panel of 26 genes involved in EGFR signaling pathway and colorectal carcinogenesis. RESULTS: Mutational status of primary tumors and metastatic lesions was highly concordant in TP53, APC, CTNNB1, KRAS, PIK3CA, PTEN, and FBXW7 genes. Metastatic samples harbor significantly more mutations than primary tumors. Potentially negative predictive value of FBXW7 mutations in relationship to anti-EGFR treatment outcomes was confirmed. Finally, new occurrences of activating KRAS mutations were identified in a group of patients initially determined as wild-type RAS by routinely used qPCR-based RAS mutational tests. All newly detected activating KRAS mutations most likely led to cetuximab treatment failure. CONCLUSION: The results of the present study suggest a need of careful consideration of previously published results of anti-EGFR-targeted therapy with regard to potentially inaccurate diagnostic tools used in the past. Based on our findings, we recommend more extensive use of next-generation sequencing testing in daily clinical practice, as it brings a significant added value in terms of validity of the diagnostic procedure.
Keywords: cetuximab; next-generation sequencing; KRAS; colorectal cancer; resistance to anti-EGFR therapy; FBXW7